1996
DOI: 10.1136/gut.38.6.916
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated GLP-1 secretion in obesity: cause or consequence?

Abstract: Background-Hypersecretion of insulinotropic factors such as glucose dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (7-36)amide (GLP-1) have been postulated to account for the hyperinsulinaemia of obesity. Aims-To examine the role of GLP-1 and GIP in obese women and matched controls. Subjects-Six lean and six obese women subjects matched for age. Methods-The gut hormone, plasma glucose, and serum triglyceride responses were studied over 180 minutes after oral carbohydrate and fat meals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
194
8
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(225 citation statements)
references
References 12 publications
13
194
8
7
Order By: Relevance
“…In some studies 19–22 , GLP‐1 levels in response to oral carbohydrate or a meal have been reduced in obese patients; this may have contributed to the decline in HbA1c reduction with this drug with increasing BMI, although which feature of the obese state is causally related to the inhibition of GLP‐1 release remains unknown. Circulating free fatty acids have been suggested to inhibit GLP‐1 release and stimulate GIP secretion 20 . However, Verdich et al.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies 19–22 , GLP‐1 levels in response to oral carbohydrate or a meal have been reduced in obese patients; this may have contributed to the decline in HbA1c reduction with this drug with increasing BMI, although which feature of the obese state is causally related to the inhibition of GLP‐1 release remains unknown. Circulating free fatty acids have been suggested to inhibit GLP‐1 release and stimulate GIP secretion 20 . However, Verdich et al.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,37 Thus, it can be speculated that the lower GLP-1 response in obese subjects after a meal, may result in a shorter period of inter-meal satiety and more frequent food intake to maintain an appropriate individual satiety level. Therefore, GLP-1 administered to obese subjects, may have an anorectic Figure 5 Mean AE s.e.m.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Obese subjects may have an attenuated release of GLP-1 in response to meals. 13,14 In a previous study, we demonstrated that intravenous infusion of GLP-1, for four hours, to six obese subjects, resulted in lower hunger ratings over four hours after the start of infusion. Concomitantly with the start of GLP-1 infusion, a meal was eaten on a universal eating monitor.…”
Section: Introductionmentioning
confidence: 99%
“…However, whereas previous studies have found that dietary fat is a potent stimulus for gastrointestinal peptides secretion, we found a potent reduction in only GIP, with just a modest reduction in GLP-1 and PYY , when most of the fat was removed from the diet. This may be explained in part by the overweight status of our subjects, because secretion of GLP-1 and PYY in response to fat ingestion has been found to be attenuated in obesity (24,33). Unlike GLP-1 and PYY , GIP does not appear to be affected by an individual's body weight (33), which may explain why we found a more profound attenuation in GIP concentration when fat was removed from the meal.…”
Section: Discussionmentioning
confidence: 66%
“…This may be explained in part by the overweight status of our subjects, because secretion of GLP-1 and PYY in response to fat ingestion has been found to be attenuated in obesity (24,33). Unlike GLP-1 and PYY , GIP does not appear to be affected by an individual's body weight (33), which may explain why we found a more profound attenuation in GIP concentration when fat was removed from the meal. It is important to acknowledge that the effect of removing fat from the meal on the secretion of these peptides cannot clearly be differentiated from the effect of the reduction in total energy that was delivered through the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 66%